Long non-coding RNA DUXAP8 promotes the cell proliferation, migration, and invasion of papillary thyroid carcinoma via miR-223-3p mediated regulation of CXCR4. Issue 1 (1st January 2021) - Liu, Yan; Zhang, Hejia; Wang, Hui; Du, Jiarui; Dong, Peng; Liu, Meihan; Lin, Yuanqiang
ABSTRACT: Papillary thyroid carcinoma (PTC) is a differentiated type of thyroid malignancy with a high incidence. Long non-coding RNA (lncRNA) DUXAP8 has been reported to participate in the proliferation, migration, and invasion of several cancer types. However, its association with PTC has not yet been reported. The current study aimed to investigate the role of DUXAP8 in PTC and revealed the underlying mechanisms. The expression of DUXAP8 was knocked down in two PTC cell lines and the effects of DUXAP8 on the PTC biological behavior were examined by cell counting kit-8 (CCK-8), wound healing, and transwell invasion assays. Luciferase reporter assay was used to detect the binding activity between miR-223-3p and DUXAP8. We found that knockdown of DUXAP8 inhibited the proliferation, migration, and invasion of PTC cells. DUXAP8 could sponge miR-223-3p through the specific binding site. CXCR4 was a target of miR-223-3p. The malignant phenotypes of the PTC cells were suppressed by the over-expression of miR-223-3p. Moreover, miR-223-3p inhibition or CXCR4 over-expression partly restored the proliferation, migration, and invasion activities of DUXAP8-downregulated PTC cells. The results evidenced that DUXAP8 acted as an oncogene in PTC, these effects seemed to partly dependent on the miR-223-3p/CXCR4 axis. Graphical abstract: uf0001